Analysis of expression of immunohistochemical markers of apoptosis and proliferation in the hippocampus of rats with experimental cardiomyopathy. - Koldunov, V. V.; Rodins’kij, O. G.; Kozlova, Yu. V.; Gerbas, T. Yu. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. To date, the question of cerebrovascular complications of cardiovascular disease remains unresolved. Objective. Evaluation of the expression of apoptosis and proliferation markers in different areas of the rat hippocampus in experimental cardiomyopathy. Methods. The material was the brain of male Wistar rats of experimental (doxorubicin injection) and control (injection with 0.9% solution of NaCl) groups. For immunohistochemical studies primary antibodies to р53, Bax, Bcl-2, caspase-3 were used. Results. 5 weeks after the first administration of doxorubicin positive reaction with proliferation marker Ki-67 and apoptosis marker caspase-3 was revealed in the hippocampal zones CA1, CA2 and DG. Proliferative response was observed mainly in endothelial cells of the major blood vessels and capillaries, which may indicate a compensatory response to circulatory hypoxia. Also immunopositive gliocytes were noticed. A small number of caspase-3-positive cells evidenced the residual effects of apoptosis. Conclusion. Positive responses of hippocampal neurons for immunohistochemical markers, particularly of pyramidal layer in fields CA1, CA3 and DG, evidenced that the experimental development of progressive cardiomyopathy results in the hippocampal endothelial proliferation in response to hypoxia with simultaneous glial proliferation.